PENGARUH KOMPENSASI, KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN BAGIAN KANTOR PADA PT. SINAR REKSA KENCANA (MENTARI GROUP) KABUPATEN INDRAGIRI HULU - Dewi Gusvita Ita i; Hendriani Susi; Ningsih Suryati Dewita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of compensation, leadership andwork environment on job satisfaction of office employees at PT. Sinar ReksaKencana (Mentari Group) Indragiri Hulu Regency. The population in this studyincludes all employees of the office, amounting to 72 people. Primary data wascollected by using a questionnaire as an instrument to prove the results of thestudy, to test the hypothesis in this study using multiple linear analysis with thehelp of the SPSS program. The sampling technique that has been selected is thecensus method (72 employees at PT. Sinar Reksa Kencana (Mentari Group)Indragiri Hulu Regency. The results showed that: 1) there was a positive andsignificant effect of compensation, leadership and work environment on jobsatisfaction of office employees at PT. Sinar Reksa Kencana (Mentari Group)Indragiri Hulu Regency, 2) there is a positive and partial effect of compensationon job satisfaction of office employees at PT. Sinar Reksa Kencana (MentariGroup) Indragiri Hulu Regency. 3) there is a positive and partial influence ofleadership on job satisfaction of office employees at PT. Sinar Reksa Kencana(Mentari Group) Indragiri Hulu Regency. 4) there is a positive and partial effectof the work environment on job satisfaction of office employees at PT. Sinar ReksaKencana (Mentari Group) Indragiri Hulu Regency. Keywords: Compensation, Leadership, Work Environment, Job Satisfaction